Aplicação da lei de Bradford à literatura técnica sobre ferrovia: análise de periódicos e avaliação da base de dados da Rede Ferroviária Federal S.A. - Coutinho, Eliana (1990)
The Bradford’s law –a bibliometric law- is applied to periodicals indexed in the RFFSA (Brazilian Federal Railways Network) data base, specialized in railways. Besides the periodicals productivity, the world bibliographic production about the area is showed by country and language, with the Brazilian position emphasized. The data base evaluation is made through its product – LISTA DE ARTIGOS SELECIONADOS – secondary source of railway literature, checking the indexing degree of the specialized articles published in the Bradford’s distribution periodicals. Other secondary sources of the area identified, their indexed periodicals are compared with the titles included in LISTA DE ARTIGOS SELECIONADOS and their accessibility in Brazilian libraries is verified. As conclusion, the author demonstrates that LISTA DE ARTIGOS SELECIONADOS is the only secondary source on railways available in the western world and presents elements to establish politicies for periodicals selection, acquisition and indexing.